Pretreatment liquid for magnesium alloy coating processing and application thereof

Chemical deposition treatment of the surface of magnesium alloy by a pretreatment liquid containing metal salts, organic phosphonic acids, activators and surfactants, the problems of poor binding force and high porosity between the magnesium alloy plating and the matrix are solved, and the porosity of the magnesium alloy plating layer is significantly improved Corrosion resistance of the coating.

CN119194431APending Publication Date: 2024-12-27SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411307365.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The pre-treatment process of magnesium alloys during electroless plating or electroplating is complicated, the bonding force between the plating layer and the substrate is poor, and the porosity of the plating layer is large, resulting in poor corrosion resistance.

Method used

A one-step magnesium alloy plating pretreatment solution, including metal salts, organic phosphonic acids, activators, film forming promoters and surfactants, is used to form a metal pretreatment layer through chemical deposition pretreatment to ensure the plating and substrate high binding force and low porosity.

Benefits of technology

The high bonding force between the plating and the substrate is achieved (not less than 6MPa) and low porosity (less than 1/cm2), which significantly improves the corrosion resistance of the plating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194431A_ABST
    Figure CN119194431A_ABST
Patent Text Reader

Abstract

The invention discloses pretreatment liquid for magnesium alloy coating processing and application of the pretreatment liquid. The pretreatment liquid comprises metal salt, organic phosphonic acid, an activating agent, a film forming accelerant and a surface active agent. The pH value of the pretreatment liquid is 1.0 to 6.0. The magnesium alloy pretreatment liquid is improved, one or more special organic phosphonic acid is selected to be complexed with metal ions, and then a chemical deposition layer with good catalytic activity is formed on the surface of the magnesium alloy through the synergistic effect of the complexing agent, the surfactant and the film-forming accelerant, and even under the condition of the pretreatment liquid with the low pH value, the chemical deposition layer has good catalytic activity. According to the present invention, the effective chemical deposition of the organic phosphonic acid and the metal ions can still be achieved under the promotion of the activator, such that the one-step pretreatment of the activation and the metal ion chemical deposition in the fluorine environment is achieved, and the metal coating is prepared in the conventional chemical plating solution or the electroplating solution so as to obtain the high bonding strength metal coating on the magnesium alloy surface, the binding force of the plating layer and the base body is not lower than 6 MPa, and the porosity of the plating layer is lower than 1 / cm < 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy processing and preparation, and in particular to a pretreatment liquid for magnesium alloy coating processing and application thereof. Background Art

[0002] Magnesium and magnesium alloys are widely used in aviation, machinery, transportation, electronics, military and medical equipment industries due to their excellent properties such as good specific strength, specific stiffness and damping resistance, as well as high toughness, high biocompatibility and good degradability. However, due to the low surface hardness, high friction coefficient, poor wear resistance, high chemical activity, and easy oxidation of the surface of magnesium alloys, the oxide film produced under natural conditions is porous and cannot play a role in corrosion protection for magnesium alloys. In order to improve the friction and wear properties and corrosion resistance of magnesium alloys, there are currently two main methods for improvement: one is to improve the specific properties by improving the alloy structure, and the alloying design is very complex and the investment cost is high; the other is material surface modification, including chemical conversion, anodizing, cold spraying, metal electroplating, chemical plating and other methods. Among them, chemical plating and electroplating are surface modification methods commonly used for magnesium alloys to improve the wear resistance of materials. Chemical plating and electroplating layers have high chemical stability, fine crystallization, low porosity, uniform coating, and are particularly suitable for complex shapes and inner holes. After heat treatment, the hardness of the coating may even be comparable to that of hard chromium plating, and it has good corrosion resistance and wear resistance.

[0003] However, due to the high electronegativity of magnesium alloy, it is extremely active and quickly forms a loose oxide film in the air. The PB ratio is 0.99<1, and it cannot form an effective and stable protective film, which leads to the continuous development of the corrosion reaction of magnesium alloy. The poor corrosion resistance of magnesium alloy is the main factor limiting the application of magnesium alloy. This oxide film also seriously blocks the firm bonding of the metal coating and the substrate, and also increases the porosity of the coating. If the surface of magnesium alloy is directly electroplated with nickel and electroplated with metal layer, the adhesion between the coating and the substrate is very poor, resulting in peeling and shedding of the coating, and poor corrosion resistance and large porosity of the coating.

[0004] In this regard, before chemical plating or electroplating of magnesium alloys, a relatively complex multi-step pre-treatment process is often adopted, such as sandblasting, grinding, pickling, multiple zinc immersion, phosphating, activation, pre-plating and micro-arc oxidation. Even so, the bonding strength between the prepared coating and the substrate is still not very ideal. After cross-scratching and pulling with tape, it was found that a large amount of metal coating was adhered to the tape. The coating bonding strength was low when tested by the pulling method, generally lower than 5MPa, indicating that the coating bonding strength needs to be improved. The prepared coating has a large porosity. After 24 hours of standard neutral salt spray test, the coating showed severe corrosion and blistering, indicating poor corrosion resistance. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a one-step pretreatment liquid for magnesium alloy coating processing and its application, so as to solve the problems in the prior art that the pretreatment procedures for chemical plating or electroplating of magnesium alloy are complicated, the bonding strength between the coating and the substrate is poor, and the porosity of the coating is large.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A one-step pretreatment solution for magnesium alloy coating processing, the pretreatment solution comprising a metal salt, an organic phosphonic acid, an activator, a film-forming promoter and a surfactant;

[0008] Among them, the metal elements in the metal salt include one or a combination of zinc, cobalt, silver, nickel, palladium and copper, and in the pretreatment solution, the concentration of metal ions is 0.01-2.0 mol / L; the organic phosphonic acid is an organic compound containing a -(PO3H2) functional group, and in the pretreatment solution, the concentration of the organic phosphonic acid is 0.1-2.0 mol / L, and the molar ratio of the organic phosphonic acid to the metal ions in the metal salt is 0.5-20.0; the activator is a fluorine-containing inorganic acid or salt, and in the pretreatment solution, the concentration of the activator is 0.02-1.0 mol / L; the film-forming promoter is an oxidant that promotes film formation, and in the pretreatment solution, the promoter concentration is 0.2-10.0 g / L; the surfactant includes one or more of a fluorocarbon surfactant, an alkyl glycoside, and a sulfonic acid anionic surfactant, and in the pretreatment solution, the surfactant concentration is 0.1-5.00 g / L; the pH value of the pretreatment solution is 1.0-6.0.

[0009] Preferably, the anion of the metal salt includes one or a combination of citrate, sulfate, chloride, nitrate, molybdate, acetate, borate, oxalate, gluconate, and glycine.

[0010] Preferably, the organic phosphonic acid comprises one or a combination of several of alkylphosphonic acid, phytic acid, diethylenetriaminepenta(methylenephosphonic acid), phosphinocarboxylic acid, ethylenediaminetetra(methylenephosphonic acid), 2-hydroxyphosphonoacetic acid, aminomethylphosphonic acid, vinylphosphonic acid, hexamethylenediaminetetra(methylenephosphonic acid), aminotri(methylenephosphonic acid), hydroxyethylidene diphosphonic acid and 1-aminophosphonic acid and their salts; the salt comprises one or a combination of several of ammonium salt, sodium salt and potassium salt.

[0011] Preferably, the alkylphosphonic acid is one of hexylphosphonic acid, octylphosphonic acid, decylphosphonic acid, dodecylphosphonic acid, tetradecylphosphonic acid, hexadecylphosphonic acid and octadecylphosphonic acid.

[0012] Preferably, the activator includes one or a combination of HF, NH4F, NH4HF2, NaF, NaHF2, KF, KHF2, MgF2, BaF2, NiF2, CoF2, and ZnF2.

[0013] Preferably, the film-forming promoter includes hydrogen peroxide, sodium m-nitrobenzene sulfonate, sodium nitroterephthalate; and one or a combination of nitric acid, molybdic acid, chloric acid and their salts; the salt is one of ammonium salt, sodium salt and potassium salt.

[0014] Preferably, the pH value of the pretreatment liquid is adjusted by a pH adjusting agent, which is an inorganic acid and alkali, and plays a role in adjusting the pH value of the pretreatment liquid to ensure that the pH value of the pretreatment liquid is 1.0-6.0. The pH adjusting agent includes one or a combination of H2SO4, HNO3, HCl, HF, NH4 HF2, NaHF2, KHF2, NaHSO4, KHSO4, NH4HSO4, NaOH, KOH, NH3·H2O, K2CO3, Na2CO3, (NH4)2CO3.

[0015] The present invention provides an application of a pretreatment liquid for magnesium alloy coating processing. The pretreatment liquid for magnesium alloy coating processing performs chemical deposition pretreatment on a magnesium alloy substrate, and then performs electroplating or chemical plating to finally form a metal coating.

[0016] Preferably, after the magnesium alloy substrate is subjected to chemical deposition pretreatment by the pretreatment liquid for magnesium alloy plating processing, a metal pretreatment layer is formed on the surface of the magnesium alloy substrate, and the thickness of the metal pretreatment layer is 1 to 10 μm.

[0017] Preferably, the chemical deposition pretreatment is:

[0018] The magnesium alloy substrate is placed in the pretreatment solution and pretreated at 20 to 90° C. for 2 to 20 minutes.

[0019] Preferably, the bonding strength between the metal coating and the substrate is not less than 6 MPa, and the surface porosity of the coating is less than 1 cell / cm 2 .

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention improves the magnesium alloy pretreatment solution by selecting one or more special organic phosphonic acids to complex with metal ions, and then synergizing with activators, surfactants and film-forming promoters to form a chemical deposition layer with good catalytic activity on the surface of the magnesium alloy. Even under the condition of a pretreatment solution with a relatively low pH value, effective chemical deposition of organic phosphonic acid and metal ions can still be achieved under the promotion of the activator, thereby realizing a one-step pretreatment of activation in a fluorine environment and chemical deposition of metal ions.

[0022] 2. The present invention also ensures the effective wetting and chelation of the coating to the magnesium alloy substrate under low pH conditions by selecting appropriate surfactants and film-forming promoters, thereby obtaining a metal protective coating with high bonding strength, ensuring that the bonding strength between the coating and the substrate is not less than 6MPa, and the surface porosity of the coating is less than 1 / cm 2 , improving the bonding effect between the coating and the substrate while improving the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart of the preparation of the magnesium alloy surface coating based on the pre-plating solution of the present invention.

[0024] Figure 2 It is a schematic structural diagram of the preparation of the magnesium alloy surface coating based on the pre-plating solution of the present invention.

[0025] Figure 3 This is a graph showing the bonding strength test results of the nickel-plated layer of the AZ31B magnesium alloy in Example 1.

[0026] Figure 4 The SEM images of the surface (4a) and cross-section (4b) of the nickel-plated layer of the AZ31B magnesium alloy of Example 1 are shown.

[0027] Figure 5 This is the EDS energy spectrum of the embedded cross section of the nickel-plated layer of AZ31B magnesium alloy in Example 1; wherein a is the Mg element and b is the Ni element.

[0028] Figure 6 This is a graph showing the porosity test results of the nickel plating layer on the surface of the AZ31B magnesium alloy of Example 1.

[0029] Figure 7 The bonding strength test diagram (7a) and porosity diagram (7b) of the nickel-plated layer of AZ31B magnesium alloy of blank control example 1 are shown.

[0030] Figure 8 This is a graph showing the bonding strength of the nickel-plated layer of the AZ31B magnesium alloy of Comparative Example 1; wherein a and c are manganese ions, and b and d are iron ions.

[0031] Fig. 9This is a graph showing the porosity test results of the nickel-plated layer of AZ31B magnesium alloy in comparative example 1.

[0032] Fig.10 The bonding strength test diagram (10a) and porosity diagram (10b) of the nickel-plated layer of AZ91D magnesium alloy of Example 2 are shown.

[0033] Fig.11 These are SEM images of the surface (11a) and cross-section (11b) of the nickel-plated layer of the AZ91D magnesium alloy of Example 2.

[0034] Fig.12 This is the EDS energy spectrum of the cross section of the nickel-plated layer of AZ91D magnesium alloy in Example 2; wherein a is the Mg element and b is the Ni element.

[0035] Fig.13 The bonding strength test results of the nickel-plated layer of AZ91D magnesium alloy of blank control example 2.

[0036] Fig.14 Comparative Example 2: AZ91D magnesium alloy nickel plating layer bonding strength test graph (14a) and porosity graph (14b).

[0037] Fig.15 The bonding strength test diagram (15a) and porosity diagram (15b) of the nickel-plated layer of AM50A magnesium alloy of Example 3 are shown.

[0038] Fig.16 The SEM images are of the surface (16a) and the embedded cross section (16b) of the chemically plated nickel layer of the AM50A magnesium alloy of Example 3.

[0039] Fig.17 This is the EDS energy spectrum of the AM50A magnesium alloy nickel-plated layer inlaid section of Example 3; wherein a is the Mg element and b is the Ni element.

[0040] Fig.18 This is the bonding strength test result diagram of the nickel-plated layer of AM50A magnesium alloy of blank control example 3.

[0041] Fig.19 The bonding strength test diagram (19a) and porosity diagram (19b) of the nickel-plated layer of AM50A magnesium alloy of comparative example 3 are shown.

[0042] Fig. 20 This is a graph showing the bonding strength test results of the nickel-plated layer of AZ31T magnesium alloy in Example 4.

[0043] Fig.21 This is the bonding strength test result diagram of the nickel-plated layer of AZ31T magnesium alloy of blank control example 4.

[0044] Fig. 22The AZ31T magnesium alloy nickel plating layer appearance diagram (22a), the cross-hatch test result diagram (22b) and the porosity test diagram (22c) of comparative example 4 are shown.

[0045] Fig.23 The bonding strength test diagram (23a) and porosity diagram (23b) of the nickel-plated layer of AZ91D magnesium alloy of Example 5 are shown.

[0046] Fig.24 The bonding strength test diagram (24a) and porosity diagram (24b) of the nickel-plated layer of AZ91D magnesium alloy of blank control example 5 are shown.

[0047] Fig.25 The bonding strength test diagram (25a) and porosity diagram (25b) of the nickel-plated layer of AZ91D magnesium alloy of comparative example 5 are shown.

[0048] Fig.26 The bonding strength test diagram (26a) and porosity diagram (26b) of the nickel-plated layer of AM50A magnesium alloy of Example 6 are shown.

[0049] Fig. 27 The bonding strength test diagram (27a) and porosity diagram (27b) of the nickel-plated layer of AM50A magnesium alloy of blank control example 6 are shown.

[0050] Fig.28 The bonding strength test diagram (28a) and porosity diagram (28b) of the nickel-plated layer of AM50A magnesium alloy of comparative example 6 are shown. DETAILED DESCRIPTION

[0051] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.

[0052] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0053] 1. A pretreatment solution for magnesium alloy coating processing

[0054] The pretreatment solution of the present invention comprises a metal salt, an organic phosphonic acid, an activator, a film-forming promoter and a surfactant; wherein the metal element in the metal salt comprises one or a combination of zinc, cobalt, silver, nickel, palladium and copper, and the concentration of the metal ions in the pretreatment solution is 0.01 to 2.0 mol / L; the organic phosphonic acid is an organic compound containing a -(PO3H2) functional group, the concentration of the organic phosphonic acid is 0.1 to 2.0 mol / L, and the molar ratio of the organic phosphonic acid to the metal ions in the metal salt is 0.5 ~20.0; the activator is a fluorine-containing inorganic acid or salt, and in the pretreatment liquid, the activator concentration is 0.02~1.0mol / L; the film-forming promoter is an oxidant that promotes film formation, and in the pretreatment liquid, the promoter concentration is 0.2~10.0g / L; the surfactant includes one or more of a fluorocarbon surfactant, an alkyl glycoside, and a sulfonic acid anionic surfactant, and in the pretreatment liquid, the surfactant concentration is 0.1~5.00g / L; the pH value of the pretreatment liquid is 1.0~6.0.

[0055] After conducting an in-depth study on the pretreatment process of magnesium alloys, the present invention found that the pretreatment process of magnesium alloys in the prior art is very complicated, usually involving multiple steps, such as sandblasting, grinding, pickling, multiple zinc immersion, phosphating, activation, pre-plating and micro-arc oxidation. However, even with these multi-step treatment methods, the bonding force between the obtained coating and the magnesium alloy substrate is still low, and the porosity is high. On this basis, the present invention conceives to simplify the pretreatment process, and further considers integrating the activation process of the magnesium alloy substrate with the metal ion chemical deposition process, thereby simplifying the pretreatment process, but it is necessary to consider ensuring the connection effect between the coating and the substrate. The present invention further found that after conventional pretreatment, a metal pretreatment layer will be formed on the surface of the magnesium alloy substrate, but this metal pretreatment layer must be formed in a specific pH range. When the pH value is too low, the magnesium alloy substrate will undergo a violent hydrogen evolution reaction. Since the stability constant between the complexing agent and the metal ion is significantly reduced, the chemical reaction is unstable, and the bonding force between the pretreated metal layer and the substrate is poor. When the pH value is too high, the magnesium alloy substrate has poor solubility with the metal ions. After these insoluble substances are mechanically covered on the substrate surface, they will also seriously affect the bonding force between the coating and the substrate. In response to this technical problem, the present invention has conducted in-depth research on the pretreatment liquid and found that one or more special organic phosphonic acids are selected to complex with metal ions, and then synergistically with activators, surfactants and film-forming promoters, a chemical deposition layer with good catalytic activity can be formed on the surface of the magnesium alloy. Even under the condition of a pretreatment liquid with a lower pH value, effective chemical deposition of organic phosphonic acid and metal ions can still be achieved under the promotion of the activator. Not only that, it can also achieve a one-step pretreatment of activation and chemical deposition of metal ions under a fluorine environment, and ultimately achieve the purpose of optimizing and simplifying the pretreatment process. In addition, the present invention also found that by selecting appropriate surfactants and film-forming promoters, effective wetting and chelation of the coating to the magnesium alloy substrate under low pH conditions can be ensured, thereby obtaining a metal protective coating with high bonding strength, ensuring that the adhesion between the coating and the substrate is not less than 6MPa, and the surface porosity of the coating is less than 1 / cm 2 , ultimately ensuring a firm bond between the coating and the substrate while significantly improving the corrosion resistance of the coating, and has very good application prospects.

[0056] In some embodiments of the present invention, in the pretreatment solution, the metal ion concentration in the metal salt is 0.01-2.0 mol / L. If the metal ion concentration is too low, it is not enough to deposit on the surface of the magnesium alloy substrate to form a metal pretreatment layer, thereby affecting the connection effect between the coating and the substrate; and if the metal ion concentration is too high, the metal pretreatment layer will form too quickly, resulting in a loose and non-dense metal pretreatment layer, which reduces the bonding strength between the coating and the substrate. In the pretreatment solution, the anion of the metal salt includes one or a combination of citrate, sulfate, chloride, nitrate, molybdate, acetate, borate, oxalate, gluconate, and glycine. Therefore, in the pretreatment solution, the metal ion concentration in the metal salt can be 0.01mol / L, 0.02mol / L, 0.03mol / L, 0.05mol / L, 0.07mol / L, 0.09mol / L, 1.0mol / L, 1.5mol / L, 2.0mol / L, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0057] In some embodiments of the present invention, the organic phosphonic acid is an organic compound containing a -(PO3H2) functional group, and the organic phosphonic acid includes alkylphosphonic acid, phytic acid, diethylenetriaminepenta(methylenephosphonic acid), phosphine carboxylic acid, ethylenediaminetetramethylenephosphonic acid, 2-hydroxyphosphonoacetic acid, aminomethylphosphonic acid, vinylphosphonic acid, hexamethylenediaminetetramethylenephosphonic acid, aminotri(methylenephosphonic acid), hydroxyethylidene diphosphonic acid and 1-aminophosphonic acid and salts thereof, one or more combinations thereof; Here, the salts include one or more combinations thereof of ammonium salts, sodium salts and potassium salts. More preferably, the alkylphosphonic acid is one of hexylphosphonic acid, octylphosphonic acid, decylphosphonic acid, dodecylphosphonic acid, tetradecylphosphonic acid, hexadecylphosphonic acid and octadecylphosphonic acid. The molar ratio of the organic phosphonic acid to the metal ions in the metal salt is an important parameter affecting the bonding strength of the coating. If the molar ratio is too low, the generated metal pretreatment layer is loose, and if the molar ratio is too high, the metal pretreatment layer will be generated too slowly, resulting in incomplete coverage of the metal pretreatment layer. Both of these situations will affect the bonding strength and porosity of the coating. Therefore, the molar ratio of the organic phosphonic acid to the metal ions in the metal salt can be 0.5, 1.0, 5.0, 5.5, 5.6, 5.7, 5.8, 6.0, 6.6, 6.7, 6.8, 6.9, 7.0, 7.5, 8.0, 9.0, 10.0, 15.0, 18.0, 20.0, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0058] In some embodiments of the present invention, the activator is a fluorine-containing inorganic acid or salt, and the activator includes one or a combination of HF, NH4F, NH4HF2, NaF, NaHF2, KF, KHF2, MgF2, BaF2, NiF2, CoF2, and ZnF2. If the concentration of the activator in the pretreatment solution is too low, the activation degree is low, and the metal pretreatment layer is not fully covered. If the concentration of the activator is too high, the substrate will be corroded to form corrosion pits. At the same time, the present invention also finds that the coating formed by using an activator other than the type described in the present invention is often incomplete, peeling, cracking, rough, and powdering. In the pretreatment solution, the concentration of the activator is 0.02-1.0 mol / L, and can be further 0.02 mol / L, 0.4 mol / L, 0.5 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0059] In some embodiments of the present invention, the film-forming promoter is an oxidant that promotes film formation, and the film-forming promoter includes hydrogen peroxide, sodium m-nitrobenzene sulfonate, sodium nitroterephthalate; and one or more combinations of nitric acid, molybdic acid, chloric acid and their salts; the salt is one of ammonium salt, sodium salt and potassium salt. In the pretreatment solution, if the concentration of the film-forming promoter is too low, the metal pretreatment layer will not be fully covered, and if the concentration of the film-forming promoter is too high, the formation of the metal pretreatment layer may stagnate. The concentration of the film-forming promoter is 0.2 to 10.0 g / L, and can be further 0.2 g / L, 1.96 g / L, 1.65 g / L, 1.07 g / L, 2.25 g / L, 1.13 g / L, 3.0 g / L, 3.5 g / L, 5.0 g / L, 5.5 g / L, 7.0 g / L, 8.5 g / L, 10.0 g / L, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0060] In some embodiments of the present invention, the surfactant is a wetting agent, including one or more of a fluorocarbon surfactant, an alkyl glycoside, and a sulfonic acid anionic surfactant. In the pretreatment solution, the surfactant concentration is 0.1 to 5.00 g / L, and can be further 0.1 g / L, 0.2 g / L, 0.4 g / L, 0.5 g / L, 0.8 g / L, 1.0 g / L, 3.0 g / L, 4.5 g / L, 5.0 g / L, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0061] In some embodiments of the present invention, the pH value of the pretreatment liquid is adjusted by a pH adjusting agent, and the pH adjusting agent is an inorganic acid and a base, which plays a role in adjusting the pH value of the pretreatment liquid to ensure that the pH value of the pretreatment liquid is 1.0 to 6.0. Wherein, the pH adjusting agent includes one or a combination of H2SO4, HNO3, HCl, HF, NH4 HF2, NaHF2, KHF2, NaHSO4, KHSO4, NH4HSO4, NaOH, KOH, NH3·H2O, K2CO3, Na2CO3, (NH4)2CO3. Too low pH will cause the magnesium alloy substrate to be rapidly corroded and the pretreatment layer to become powdery; too high pH will reduce the ability of organic phosphonic acid to bind metal ions, making it difficult to form a pretreatment layer. The pH value can be 1.0, 1.9, 2.0, 2.3, 2.5, 2.6, 2.7, 5.0, 6.0, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the implementation scheme, any of the above ranges can be combined with any other ranges.

[0062] 2. Application of a pretreatment solution for magnesium alloy coating processing

[0063] like Figure 1 and Figure 2 As shown, the magnesium alloy substrate is subjected to chemical deposition pretreatment by the pretreatment liquid for magnesium alloy coating processing of the present invention, and then electroplating or chemical plating is performed. The electroplating or chemical plating is a conventional processing procedure in the prior art, and finally a metal pretreatment layer and a metal coating are sequentially formed on the surface of the magnesium alloy substrate material, and the formed coating can have an excellent connection effect with the magnesium alloy substrate.

[0064] In some embodiments of the present invention, after the magnesium alloy substrate is subjected to chemical deposition pretreatment by the magnesium alloy plating processing pretreatment liquid, a metal pretreatment layer is formed on the surface of the magnesium alloy substrate, and the thickness of the metal pretreatment layer is 1 to 10 μm.

[0065] In some embodiments of the present invention, the one-step chemical deposition pretreatment is: placing the magnesium alloy substrate in the pretreatment solution, and pretreatment for 2 to 20 minutes at 20 to 90°C. If the pretreatment temperature is too low, it will make it difficult to form a metal pretreatment layer; if it is too high, it will cause corrosion of the magnesium alloy substrate and the pretreatment layer will become powdery. Therefore, the pretreatment temperature can be 20 to 90°C, and is further preferably 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C, etc., and all ranges and sub-ranges between the above values; if the pretreatment time is too short, the coating will be incomplete; if the pretreatment time is too long, the coating will be rough and a large number of nickel nodules will be generated, so it can be 2min, 5min, 10min, 15min, 20min, etc., and all ranges and sub-ranges between the above values. It should be understood that in the implementation scheme, any of the above ranges can be combined with any other ranges.

[0066] 3. Examples and Comparative Examples

[0067] Example 1

[0068] The AZ31B magnesium alloy is processed in the following process sequence: degreasing (depending on the situation) → water washing / blow drying → preparation of metal pretreatment layer → water washing / blow drying → chemical nickel plating → water washing / blow drying:

[0069] (1) If the magnesium alloy surface is seriously oily, the AZ31B magnesium alloy is subjected to conventional ultrasonic degreasing for 10 minutes; if the magnesium alloy is clean, this process can be omitted;

[0070] (2) After degreasing the AZ31B magnesium alloy in step (1), the alloy is cleaned and dried;

[0071] (3) The AZ31B magnesium alloy is subjected to chemical deposition treatment in a pretreatment solution, and the composition of the pretreatment solution is as follows:

[0072]

[0073] The pH value of the pretreatment solution was adjusted to 2.3 with ammonia water, and the rest was deionized water.

[0074] The AZ31B magnesium alloy is immersed in the pretreatment solution and chemically deposited at 60° C. for 5 minutes, thereby forming a pretreatment metal layer on the surface of the AZ31B magnesium alloy;

[0075] (4) After chemical deposition treatment, clean and dry;

[0076] (5) The AZ31B magnesium alloy having formed a metal pretreatment layer is subjected to chemical nickel plating, wherein the plating is performed using the HSN-100 series medium-phosphorus chemical nickel plating solution of Changzhou Chenghe New Material Technology Co., Ltd., and the plating parameters are:

[0077] Ni 2+ :6g / L

[0078] pH: 4.8

[0079] Temperature: 85℃

[0080] Time: 1 hour

[0081] (6) After chemical nickel plating, clean and blow dry.

[0082] The nickel-plated layer of the AZ31B alloy composite material prepared in Example 1 was tested for adhesive tape bonding strength by a bending method and a cross-hatch method (5 to 10 lines were drawn with a blade at intervals of about 1 mm in both the horizontal and vertical directions. When crossing, the coating should be cut through to the substrate). There was no adhesion of any coating on the tape, and the bonding strength evaluation grade was the highest grade (grade 10), indicating that the coating bonding strength was good. Figure 3 The surface of the nickel-plated layer was observed by scanning electron microscopy. The crystals were fine and there were no defects such as nickel nodules. The SEM image is shown in the attached figure. Figure 4 a; The coating was inlaid with resin and the cross section was observed with a scanning electron microscope. It was found that there was no obvious interface between the coating and the substrate. Figure 4 b, EDS element scanning of the cross section Figure 5 It was also found that there was no obvious interface between the coating and the substrate, which also shows that the coating and the substrate are well bonded. The bonding strength between the nickel coating and the substrate was tested by the pull-off method. The test result was 17.89MPa, which further shows that the coating has good bonding strength. For the porosity test, 5ml HCl and 6g NaCl were dissolved in 100ml distilled water to make a corrosion solution. After soaking for 1min, take it out, wipe off the corrosion solution, and add 10g / L chrome black T display solution. The number of pores per square centimeter was detected, and the porosity was found to be 0. Figure 6 .

[0083] Blank control example 1

[0084] An improvement is made on the basis of Example 1, the difference being that in the "chemical deposition treatment" of step (3), no metal ion "zinc sulfate" is added, and the remaining operations are the same as those of Example 1.

[0085] The nickel-plated layer of the AZ31B magnesium alloy composite material prepared in blank control example 1 is incomplete, and a part of the area is not plated with nickel. After the bonding strength test of the formed nickel-plated layer by the bending method and the cross-hatch method, the coating falls off seriously at the scratched area, as shown in the attached Figure 7 a; Porosity test, pores up to 40 / cm 2 ,like Figure 7 b.

[0086] Comparative Example 1

[0087] An improvement is made on the basis of Example 1, the difference being that in the "chemical deposition treatment" of step (3), metal ions "manganese sulfate and iron sulfate" of equal concentration are used to replace the metal ion "zinc sulfate" in Example 1, and the remaining operations are the same as in Example 1.

[0088] The nickel-plated layer on the surface of the AZ31B magnesium alloy prepared in Comparative Example 1 was relatively rough. After the bonding strength test by the cross-hatch method, it was found that the plating squares fell off and the bonding strength was poor. After the bending test, the plating had a large number of cracks, as shown in the attached Figure 8 It can be seen that whether it is manganese sulfate or iron sulfate, the coating obtained has poor bonding with the substrate; the porosity test is up to 20 / cm 2 ,like Fig. 9 This indicates that the metal ions "manganese sulfate and iron sulfate" in Comparative Example 1 cannot play a catalytic role as effectively as the metal ion "zinc sulfate" in Example 1 under a low pH environment, resulting in incomplete coverage of the metal pretreatment layer formed in the early stage, or a weak bond with the magnesium alloy substrate.

[0089] Example 2

[0090] The AZ91D magnesium alloy is processed in the following process sequence: degreasing (depending on the situation) → water washing / blow drying → preparation of metal pretreatment layer → water washing / blow drying → chemical nickel plating → water washing / blow drying:

[0091] (1) Perform conventional ultrasonic degreasing on the AZ91D magnesium alloy for 10 minutes.

[0092] (2) After degreasing, clean and dry;

[0093] (3) The AZ91D magnesium alloy is subjected to chemical deposition treatment in a pretreatment solution, and the composition of the pretreatment solution is as follows:

[0094]

[0095] The pH value of the pretreatment solution was adjusted to 2.0 with ammonia water, and the rest was deionized water.

[0096] The AZ91D magnesium alloy is immersed in the pretreatment solution and chemically deposited at 70° C. for 5 minutes, thereby forming a metal pretreatment layer on the surface of the AZ91D magnesium alloy;

[0097] (4) After chemical deposition treatment, clean and dry;

[0098] (5) The AZ91D magnesium alloy having formed a metal pretreatment layer is subjected to medium phosphorus chemical nickel plating, and the plating parameters are:

[0099] Ni 2+ :6g / L

[0100] pH: 4.8

[0101] Temperature: 85℃

[0102] Time: 1 hour

[0103] (6) After chemical nickel plating, clean and blow dry.

[0104] The nickel-plated layer of the AZ91D alloy composite material prepared in Example 2 was tested for bonding strength by the bending method and the cross-hatch method. No coating adhered to the tape, and the bonding strength evaluation grade was 10, indicating that the coating had good bonding strength. Fig.10 a, porosity test, 0 / cm 2 ,like Fig.10 b. Observe the surface of the nickel-plated layer using a scanning electron microscope. The crystals are fine and there are no defects such as nickel nodules. The SEM image is as follows Fig.11 a. The coating is inlaid with resin and the cross section is observed with a scanning electron microscope. Fig.11 b. Perform EDS element scanning on the cross section at the same time, and the energy spectrum is shown in Fig.12 It was found that there was no obvious interface between the coating and the substrate, indicating that the coating and the substrate were well bonded. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test result was 11.01MPa, further indicating that the coating and the substrate were well attached.

[0105] Blank control example 2

[0106] An improvement is made on the basis of Example 2, except that in the "chemical deposition treatment" of step (3), no organic phosphonic acid "vinylphosphonic acid, aminomethylphosphonic acid" is added, and the remaining operations are the same as those of Example 2.

[0107] The nickel-plated layer on the surface of the AZ91D magnesium alloy prepared in blank control example 2 was rough, black and gray. After the bonding strength test by the bending method and the cross-hatch method, the coating fell off seriously, and the bending part cracked and peeled. The adhesion was very poor. Fig.13 .

[0108] Comparative Example 2

[0109] An improvement is made on the basis of Example 2, the difference being that in the "chemical deposition treatment" of step (3), equal concentrations of organic phosphonic acids "di(dimethyl)phosphonic acid, trimethylphosphonic acid" are used to replace the organic phosphonic acids "vinylphosphonic acid, aminomethylphosphonic acid" in the original Example 2, and the remaining operations are the same as those in Example 2.

[0110] The nickel-plated layer on the surface of the AZ91D magnesium alloy prepared in Comparative Example 2 is relatively rough. The bonding strength test by the cross-hatch method and the bending method found that the plating squares fell off more, the plating peeled off at the bend, and the bonding strength was very poor. Fig.14a, significantly lower than Example 2. This is because the organic phosphonic acid "hexamethylenediaminetetramethylenephosphonic acid, 1-aminophosphonic acid" in Example 2 cannot effectively perform complexation like the organic phosphonic acid "vinylphosphonic acid, aminomethylphosphonic acid" in Example 2 under a very low pH environment. Porosity test, 30 / cm 2 ,like Fig.14 b.

[0111] Example 3

[0112] AM50A magnesium alloy is processed in the following process sequence: degreasing (depending on the situation) → water washing / blow drying → preparation of metal pretreatment layer → water washing / blow drying → chemical nickel plating → water washing / blow drying:

[0113] (1) Perform conventional ultrasonic degreasing on AM50A magnesium alloy for 10 minutes.

[0114] (2) After degreasing, clean and dry;

[0115] (3) AM50A magnesium alloy is placed in a pretreatment solution for chemical deposition treatment, and the pretreatment solution has the following composition:

[0116]

[0117] The pH value of the pretreatment solution was adjusted to 2.7 with ammonia water, and the rest was deionized water.

[0118] The AM50A magnesium alloy is immersed in the pretreatment solution and chemically deposited at 70° C. for 5 minutes, thereby forming a metal pretreatment layer on the surface of the AM50A magnesium alloy;

[0119] (4) After chemical deposition treatment, clean and dry;

[0120] (5) The AM50A magnesium alloy having formed a metal pretreatment layer is subjected to chemical nickel plating, wherein an alkaline low-phosphorus chemical nickel plating solution is used for plating, and the plating parameters are:

[0121] Ni 2+ :6.5g / L

[0122] pH: 7.0

[0123] Temperature: 75℃

[0124] Time: 1 hour

[0125] (6) After chemical nickel plating, clean and blow dry.

[0126] The nickel-plated layer of the AM50A alloy composite material prepared in Example 3 was tested for bonding strength by the bending method and the cross-hatch method. No coating adhered to the tape, and the bonding strength rating was 10, indicating that the coating had good bonding strength. Fig.15 a, after porosity test, 0 / cm 2 ,like Fig.15 b. The surface of the nickel-plated layer prepared in Example 3 was observed by scanning electron microscopy. The crystals were fine and there were no defects such as nickel nodules. The SEM image was as follows: Fig.16 a. The coating was inlaid with resin and the cross section was observed using a scanning electron microscope. It was found that there was no obvious interface between the coating and the substrate, such as Fig.16 b, EDS element scanning of the cross section Fig.17 , it was also found that there was no obvious interface between the coating and the substrate, which also showed that the coating and the substrate were well bonded. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test value was 16.0MPa, which further showed that the coating and the substrate were well attached.

[0127] Blank control example 3

[0128] An improvement is made on the basis of Example 3, the difference being that in the "chemical deposition treatment" of step (3), no activator "NH4HF2" is added, and the remaining operations are the same as those of Example 3.

[0129] The nickel-plated layer on the surface of the AM50A magnesium alloy prepared in blank control example 3 was incomplete and partially powdery. The adhesive strength test by bending method and cross-hatch method found that there were powdery plating particles on the tape, the plating layer fell off seriously, cracks appeared at the bend, and the surface adhesion was extremely poor. Fig.18 .

[0130] Comparative Example 3

[0131] An improvement is made on the basis of Example 3, the difference being that in the "chemical deposition treatment" of step (3), an activator "ammonium chloride" of equal concentration is used instead of the activator "NH4HF2" of Example 3, and the remaining operations are the same as those of Example 3.

[0132] Comparative Example 3 prepared AM50A magnesium alloy composite material chemical nickel plating layer, using the cross-cut test and bending test found that the coating peeling, blistering, indicating that the coating bonding is poor, such as the attached Fig.19 a; According to the porosity test, about 6 / cm 2 ,like Fig.19 b. This is because the activator "ammonium chloride" in Comparative Example 3 cannot effectively exert the activation effect like the activator "HF" in Example 3 under a low pH environment.

[0133] Example 4

[0134] The AZ31T magnesium alloy is processed in the following process sequence: degreasing (depending on the situation) → water washing / blow drying → preparation of metal pretreatment layer → water washing / blow drying → chemical nickel plating → water washing / blow drying:

[0135] (1) Perform conventional ultrasonic degreasing on the AZ31T magnesium alloy for 10 minutes.

[0136] (2) After degreasing, clean and dry;

[0137] (3) The AZ31T magnesium alloy is subjected to chemical deposition treatment in a pretreatment solution, wherein the pretreatment solution comprises the following components:

[0138]

[0139] The pH value of the pretreatment solution was adjusted to 2.5 with ammonia water, and the rest was deionized water.

[0140] The AZ31T magnesium alloy is immersed in the pretreatment solution and chemically deposited at 70° C. for 5 minutes, thereby forming a metal pretreatment layer on the surface of the AZ31T magnesium alloy;

[0141] (4) After chemical deposition treatment, clean and dry;

[0142] (5) The AZ31T magnesium alloy having formed a metal pretreatment layer is subjected to chemical nickel plating, wherein a high-phosphorus chemical nickel plating solution is used for plating, and the plating parameters are:

[0143] Ni 2+ :5.5g / L

[0144] pH: 5.8

[0145] Temperature: 55℃

[0146] Time: 1 hour

[0147] (6) After chemical nickel plating, clean and blow dry.

[0148] The nickel-plated layer on the surface of the AZ31T alloy prepared in Example 4 was tested for bonding strength by the bending method and the cross-hatch method. No coating adhered to the tape, and the bonding strength rating was 10, indicating that the coating had good bonding strength. Fig. 20 The bonding strength between the coating and the substrate was tested by the pull-off method, which was 9.54 MPa, further indicating that the coating and the substrate were well adhered.

[0149] Blank control example 4

[0150] An improvement is made on the basis of Example 4, the difference being that in the "chemical deposition treatment" of step (3), the pH adjusting agent "ammonia water" is not added to make the pH value of the pretreatment liquid 0.8, and the rest of the operations are the same as those of Example 4.

[0151] The surface chemical nickel plating layer of the AZ31T magnesium alloy composite material prepared in blank control example 4 was powdery, and the bending test specimen was broken, indicating that the bonding strength of the coating was extremely poor. Fig.21 This is because the pH adjuster "ammonia water" in blank control example 4 was not used, so the organic phosphonic acid in Example 4 could not effectively perform the complexing effect.

[0152] Comparative Example 4

[0153] An improvement is made on the basis of Example 4, the difference being that in the "chemical deposition treatment" of step (3), a pH adjusting agent "ammonia water" is used to change the pH of Example 4 so that the pH value of the pretreatment liquid is 6.5, and the rest of the operations are the same as those of Example 4.

[0154] The surface chemical nickel plating layer of the AZ31T magnesium alloy composite material prepared in Comparative Example 4 is intact, but the plating layer falls off when tested by the cross-hatch method. Fig. 22 a. Using the bending method, it was found that the coating had obvious shedding and peeling on the bending surface, as shown in the attached Fig. 22 b. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test value was 3.96MPa. Porosity test, about 25 / cm 2 ,like Fig. 22 c.

[0155] Example 5

[0156] The AZ91D magnesium alloy is processed in the following process sequence: degreasing (depending on the situation) → water washing / blow drying → preparation of metal pretreatment layer → water washing / blow drying → chemical nickel plating → water washing / blow drying:

[0157] (1) Perform conventional ultrasonic degreasing on the AZ91D magnesium alloy for 10 minutes.

[0158] (2) After degreasing, clean and dry;

[0159] (3) The AZ91D magnesium alloy is placed in a pretreatment solution for chemical deposition treatment, wherein the pretreatment solution comprises the following components:

[0160]

[0161]

[0162] The pH value of the pretreatment solution was adjusted to 2.6 with ammonia water, and the rest was deionized water.

[0163] The AZ91D magnesium alloy is immersed in the pretreatment solution and chemically deposited at 70° C. for 5 minutes, thereby forming a metal pretreatment layer on the surface of the AZ91D magnesium alloy;

[0164] (4) After chemical deposition treatment, clean and dry;

[0165] (5) The AZ91D magnesium alloy having formed a metal pretreatment layer is subjected to chemical nickel plating, wherein a low-phosphorus chemical nickel plating solution is used for plating, and the plating parameters are:

[0166] Ni 2+ :6.4g / L

[0167] pH: 5.0

[0168] Temperature: 65℃

[0169] Time: 1 hour

[0170] (6) After chemical nickel plating, clean and blow dry.

[0171] The nickel-plated layer of the AZ91D alloy composite material prepared in Example 5 was tested for bonding strength by the bending method and the cross-hatch method. No coating adhered to the tape, and the bonding strength evaluation grade was 10, indicating that the coating had good bonding strength. Fig.23 a, after porosity test, 0 / cm 2 ,like Fig.23 b. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test value was 10.89MPa, which further indicated that the coating and the substrate were well adhered.

[0172] Blank control example 5

[0173] An improvement is made on the basis of Example 5, the difference being that in the "chemical deposition treatment" of step (3), no film-forming promoter "sodium m-nitrobenzene sulfonate" is added, and the remaining operations are the same as those of Example 5.

[0174] The surface of the AZ91D magnesium alloy composite material prepared by blank control example 5 shows that the coating peels off in the bending test, and the bonding strength test is carried out by the cross-hatch method. There is a large amount of coating on the tape, indicating that the bonding strength of the coating is poor. Fig.24 a. Porosity test found that there are many pores, such as Fig.24 b. This is because the film-forming promoter "sodium m-nitrobenzene sulfonate" in the blank control example 5 was not used, so that the film-forming promoter did not play its due role in the low pH environment.

[0175] Comparative Example 5

[0176] An improvement is made on the basis of Example 5, the difference being that in the "chemical deposition treatment" of step (3), an equal concentration of film-forming promoter "potassium permanganate" is used instead of the film-forming promoter "sodium m-nitrobenzene sulfonate" of Example 5, and the remaining operations are the same as those of Example 5.

[0177] The surface chemical nickel plating layer of the AZ91D magnesium alloy composite material prepared in Comparative Example 5 is intact, but the plating layer falls off and peels off when the cross-hatch method is used. The plating layer also falls off and peels off at the bends when the bending method is used. Fig.25 a; Comparative Example 5 prepared AZ91D magnesium alloy composite material porosity test, porosity 3 / cm 2 ,like Fig.25 b. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test value was 5.64MPa.

[0178] Example 6

[0179] AM50A magnesium alloy is processed in the following process sequence: degreasing (depending on the situation) → water washing / blow drying → preparation of metal pretreatment layer → water washing / blow drying → chemical nickel plating → water washing / blow drying → electroplating nickel → water washing / blow drying:

[0180] (1) Perform conventional ultrasonic degreasing on AM50A magnesium alloy for 10 minutes.

[0181] (2) After degreasing, clean and dry;

[0182] (3) The AM50A magnesium alloy dried in step (2) is subjected to chemical deposition treatment in a pretreatment solution, wherein the pretreatment solution comprises the following components:

[0183]

[0184] The pH value of the pretreatment solution was 1.9 with ammonia water, and the rest was deionized water.

[0185] The AM50A magnesium alloy is immersed in the pretreatment solution and chemically deposited at 70° C. for 5 minutes, thereby forming a metal pretreatment layer on the surface of the AM50A magnesium alloy;

[0186] (4) After chemical deposition treatment, clean and dry;

[0187] (5) The AM50A magnesium alloy with a metal pretreatment layer is pre-plated with alkaline chemical nickel, and the plating parameters are:

[0188] Ni 2+ :6.8g / L

[0189] pH: 7.0

[0190] Temperature: 75℃

[0191] Time: 30 minutes

[0192] (6) After chemical nickel plating, clean and dry;

[0193] (7) The pre-nickel-plated AM50A magnesium alloy is then electroplated with nickel, wherein the electroplating nickel plating parameters are:

[0194] Ni 2+ :60g / L

[0195] pH: 4.5

[0196] Temperature: 50℃

[0197] Time: 30 minutes

[0198] The nickel-plated layer of the AM50A alloy composite material prepared in Example 6 was tested for bonding strength by the bending method and the cross-hatch method. No coating adhered to the tape, and no peeling of the coating occurred at the bend. The bonding strength rating was 10. Fig.26 a, indicating that the coating has good bonding strength, and the porosity test shows that the porosity is 0 / cm 2 ,like Fig.26 b. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test value was 12.57MPa, which further indicated that the coating and the substrate were well adhered.

[0199] Blank control example 6

[0200] An improvement is made on the basis of Example 6, except that: in the "chemical deposition treatment" of step (3), the surfactant "perfluoropolyether phosphate anionic fluorine surfactant" is not added, and the remaining operations are the same as Example 6.

[0201] The surface of the AM50A magnesium alloy composite material prepared by blank control example 6 is chemically nickel-plated, and its coating is rough. The coating peels off and a large amount of coating is stuck on the tape when the bonding strength is tested by the bending method and the cross-hatch method, indicating that the bonding strength of the coating is poor. Fig. 27 a, porosity test, about 50 / cm 2 ,like Fig. 27 b. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test value was 4.28MPa, indicating that the bonding strength of the coating was very weak without the wetting effect of the surfactant.

[0202] Comparative Example 6

[0203] An improvement is made on the basis of Example 6, the difference being that in the "chemical deposition treatment" of step (3), an equal concentration of surfactant "alkylphenol polyoxyethylene ether" is used to replace the surfactant "perfluoropolyether phosphate anionic fluorine surfactant" of Example 6, and the remaining operations are the same as those of Example 6.

[0204] The surface chemical nickel plating layer of the AM50A magnesium alloy composite material prepared in Comparative Example 6 is intact, but a small amount of plating is found to fall off and peel when tested by the cross-hatch method. Peeling occurs at the bend, indicating poor adhesion. Fig.28 a; Test porosity, the rate is about 2 / cm 2 ,like Fig.28 b. The bonding strength between the coating and the substrate was tested by the pull-off method, and the test value was 5.75MPa.

[0205] Comparative Examples 7 to 12

[0206] Before chemical nickel plating, a more conventional chemical etching or electrochemical etching treatment is used to replace the "chemical deposition treatment" in step (3) of Example 1. The etching solution components and treatment parameters used in the chemical etching or electrochemical etching treatment are as follows: the pretreatment steps described in Comparative Examples 7 to 12, and the remaining operations are the same as in Example 1:

[0207] (1) Degreasing is the same as step (1) of Example 1;

[0208] (2) After degreasing, clean and dry;

[0209] (3) chemically etching or electrochemically etching the AZ31B magnesium alloy according to the process and method described in Comparative Examples 7-12;

[0210] (4) After the AZ31B magnesium alloy is treated in step (3), it is cleaned and dried;

[0211] (5) Chemical nickel plating is the same as step (5) of Example 1.

[0212] Comparative implementation case 7 pretreatment process:

[0213] Acid washing (CrO3 180 g / L, KF 3.5 g / L, Fe(NO3)3·9H2O 40 g / L; room temperature, 2 minutes) → activation (NH4HF2

[0214] 105g / L, H3PO4 200g / L; room temperature, 2 minutes) → zinc immersion (ZnSO4·7H2O 30g / L, LiF 3g / L, Na4P2O7

[0215] 120g / L, Na2CO3 5g / L; 80℃, 8 minutes, pH=10.3) → Cyanide pre-plating copper (Cu(CN)2 40g / L, KF

[0216] 30g / L, KCN 70g / L; initial current density 6A / dm 2 , working current density 1.5A / dm 2 , 6 minutes, 55°C, pH=10).

[0217] Comparative implementation case 8 pretreatment process:

[0218] Alkali washing (NaOH 40g / L, Na2CO3 20g / L, Na3PO4 30g / L, OP-10 3mL / L; 65℃, 9 minutes) → acid washing (CrO3 125g / L, HNO3 110mL / L; room temperature, 1 minute) → primary activation (HF 200mL / L; room temperature, 6 minutes) → secondary activation (K4P2O7 80g / L, Na2CO3 35g / L, NaF 6g / L; 75℃, 8 minutes).

[0219] Comparison of pretreatment process in implementation case 9:

[0220] Acid washing (C2H2O4·2H2O 5g / L, NH4HF2 5g / L, H3PO4 25mL / L; room temperature, 1 minute) → activation (HF

[0221] 180mL / L; room temperature, 8 minutes) → zinc-nickel immersion (ZnSO4·7H2O 30g / L, NiSO4·6H2O 10g / L, K4P2O7·3H2O120g / L, Na2CO3 30g / L, KF 6g / L, citric acid 15g / L; 70℃, 10 minutes) → weak activation (NH4HF25g / L, KF 80g / L; room temperature, 5 minutes).

[0222] Comparative implementation case 10 pretreatment process:

[0223] Acid washing (Na3PO4·12H2O 10g / L, NaOH 50g / L; room temperature, 1 minute) → primary activation ((K4P2O7 150g / L, Na2CO3 20g / L, KF 11g / L; 70℃, 3 minutes) → secondary activation (NH4HF2 95g / L, H3PO4 180mL / L; room temperature, 3 minutes).

[0224] Comparative implementation case 11 pretreatment process:

[0225] Alkali washing (NaOH 30g / L, Na2CO3 40g / L, Na3PO4 30g / L, OP-10 2g / L; 75℃, 7 minutes) → acid washing (H3PO4 25mL / L, HF 180mL / L; room temperature, 1 minute) → primary zinc immersion (ZnO 80g / L, NaOH 250g / L, potassium sodium tartrate 15g / L; room temperature, 6 minutes) → zinc stripping (25% nitric acid; room temperature, 30S) → secondary zinc immersion (ZnO 100g / L, NaOH 200g / L, potassium sodium tartrate 15g / L; room temperature, 4 minutes).

[0226] Comparative implementation case 12 pretreatment process:

[0227] Micro-arc oxidation (sodium silicate 20g / L, NaOH 3g / L, disodium ethylenediaminetetraacetic acid 2g / L; 25℃, forward voltage 450V, frequency 450Hz, duty cycle 10%, treatment time 40min)→sensitization (SnCl2 4g / L, HCI 5mL / L; room temperature, ultrasonic vibration 30S)→activation (PdCl2 45mg / L, HCI 5mL / L; room temperature, ultrasonic vibration 30S)→reduction (NaH2PO2·H2O1.5g / L; room temperature, 1 minute).

[0228] Among the chemical nickel-plated layers prepared in the above-mentioned comparative examples, in comparative examples 7 and 8, the nickel-plated layers on the magnesium alloy substrates are incomplete and have obvious shedding; the chemical nickel-plated layer obtained in comparative example 9 is complete without any missing parts, but the coating is obviously shedding when tested by the bending method, indicating that the coating bonding strength is extremely poor; the chemical nickel-plated layers obtained in comparative examples 10 and 11 are apparently complete, and after the bending method test, no obvious shedding and peeling of the coating is found, but after the cross-cutting method test, a certain amount of coating shedding is found, and it can be seen that the adhesion is still poor; in comparative example 12, the chemical nickel-plated layer is complete, and the coating does not fall off after both the bending and cross-cutting methods, but the voltage required for micro-arc oxidation is relatively large, the construction requirements are relatively high, and the adhesion tested by the pulling method is only 4.9MPa. In comparative examples 7 to 12, the porosity obtained by the porosity test is greater than 1 / cm 2 .

[0229] It can be seen that in Comparative Examples 7 to 12, although two-step or multi-step methods or high-voltage special equipment are used for surface pretreatment, the final coating bonding strength and porosity are still worse than the one-step method of the present invention.

[0230] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A pretreatment solution for magnesium alloy coating processing, characterized in that: The pretreatment solution comprises a metal salt, an organic phosphonic acid, an activator, a film-forming promoter and a surfactant; The metal element in the metal salt includes one or a combination of zinc, cobalt, silver, nickel, palladium and copper, and the concentration of the metal ions in the pretreatment solution is 0.01 to 2.0 mol / L; The organic phosphonic acid is an organic compound containing a -(PO3H2) functional group. In the pretreatment solution, the concentration of the organic phosphonic acid is 0.1 to 2.0 mol / L, and the molar ratio of the organic phosphonic acid to the metal ion in the metal salt is 0.5 to 20.0; The activator is a fluorine-containing inorganic acid or salt, and in the pretreatment solution, the concentration of the activator is 0.02-1.0 mol / L; The film-forming accelerator is an oxidant that promotes film formation. In the pretreatment solution, the accelerator concentration is 0.2 to 10.0 g / L; The surfactant includes one or more of a fluorocarbon surfactant, an alkyl glycoside, and a sulfonic acid anionic surfactant. In the pretreatment solution, the surfactant concentration is 0.1 to 5.00 g / L; The pH value of the pretreatment liquid is 1.0-6.

0.

2. The pretreatment liquid for magnesium alloy coating processing according to claim 1, characterized in that: The anion of the metal salt includes one or a combination of citrate, sulfate, chloride, nitrate, molybdate, acetate, borate, oxalate, gluconate, and glycine.

3. The pretreatment liquid for magnesium alloy coating processing according to claim 1, characterized in that: The organic phosphonic acid includes one or a combination of several of alkylphosphonic acid, phytic acid, diethylenetriaminepenta(methylenephosphonic acid), phosphonic acid, ethylenediaminetetra(methylenephosphonic acid), 2-hydroxyphosphonoacetic acid, aminomethylphosphonic acid, vinylphosphonic acid, hexamethylenediaminetetra(methylenephosphonic acid), aminotri(methylenephosphonic acid), hydroxyethylidene diphosphonic acid and 1-aminophosphonic acid and their salts; the salt includes one or a combination of several of ammonium salt, sodium salt and potassium salt.

4. The pretreatment liquid for magnesium alloy coating processing according to claim 3, characterized in that: The alkylphosphonic acid is one of hexylphosphonic acid, octylphosphonic acid, decylphosphonic acid, dodecylphosphonic acid, tetradecylphosphonic acid, hexadecylphosphonic acid and octadecylphosphonic acid.

5. The pretreatment liquid for magnesium alloy coating processing according to claim 1, characterized in that: The activator includes one or a combination of HF, NH4F, NH4HF2, NaF, NaHF2, KF, KHF2, MgF2, BaF2, NiF2, CoF2, and ZnF2.

6. The pretreatment liquid for magnesium alloy coating processing according to claim 1, characterized in that: The film-forming accelerator includes hydrogen peroxide, sodium m-nitrobenzene sulfonate, sodium nitroterephthalate; and one or a combination of nitric acid, molybdic acid, chloric acid and their salts; the salt is one of ammonium salt, sodium salt and potassium salt.

7. Application of a pretreatment liquid for magnesium alloy coating processing, characterized in that: The magnesium alloy substrate is subjected to chemical deposition pretreatment using the pretreatment liquid for magnesium alloy coating processing as claimed in any one of claims 1 to 6, and then electroplating or chemical plating is performed to finally form a metal coating.

8. The use according to claim 7, characterized in that: After the magnesium alloy substrate is subjected to one-step chemical deposition pretreatment by the pretreatment liquid for magnesium alloy coating processing, a metal pretreatment layer is formed on the surface of the magnesium alloy substrate, and the thickness of the metal pretreatment layer is 1-10 μm.

9. The use according to claim 7, characterized in that: The chemical deposition pretreatment is: The magnesium alloy substrate is placed in the pretreatment solution and pretreated at 20 to 90° C. for 2 to 20 minutes.

10. The use according to claim 7, characterized in that: The bonding strength between the metal coating and the substrate is not less than 6MPa, and the surface porosity of the coating is less than 1 cell / cm 2 .

Citation Information

Cited By

  • High-corrosion-resistance amorphous alloy electroplating method

    CN122235795A